The interpretation and translation of Galatians 5:12 - D. F. Tolmie (Acta Theologica)
As is evident from commentaries on Galatians and from various English translations, scholars do not agree on the meaning, rhetorical labelling and translation of the wish expressed by Paul in Galatians 5:12. In this article various interpretations of this verse are considered; its rhetorical labelling is discussed; and suggestions are made as to the best way in which it may be translated into English.